Pemanfaatan Visual Storytelling dalam Pemasaran Affiliator di TikTok: Studi pada Konten Reizuka Ari - Jihaan Nabiilah; Suryanto Suryanto (STIKes Ibnu Sina Ajibarang, 2025)
The rapid development of affiliate marketing on social media necessitates strategies that effectively build audience trust and engagement. This study aims to analyze the application of visual storytelling and soft selling strategies in TikTok affiliate content, using a case study of 20 videos by Reizuka Ari. The research method employs qualitative content analysis, focusing on visual elements, personal narratives, audience interaction, and their relevance to engagement and trust building theories. The findings show that the use of personal visual storytelling, honest personal experience narratives, and soft selling without pressure significantly enhance emotional engagement and audience trust. Authentic testimonials, relevant captions and hashtags, as well as unobtrusive placement of affiliate links, maximize reach and conversion potential. These findings underscore the importance of content personalization in the success of affiliate marketing on short-video platforms like TikTok.